Carotid cavernous fistula after percutaneous balloon compression for trigeminal neuralgia: Endovascular treatment with coils - Gatto, Luana A. M. (Surg Neurol Int, 2017)
BACKGROUND: Percutaneous ganglyolysis treatment of trigeminal neuralgia is rarely associated with vascular complications, such as hematoma, subarachnoid hemorrhage, and stroke. Internal carotid artery injury may also occur after misguided needle placement, particularly far posteriorly or medially, resulting in carotid cavernous fistula. Anatomical variations of the foramen ovale can predispose those complications. CASE DESCRIPTION: A young woman diagnosed with trigeminal neuralgia during 11 years was submitted to a balloon rhizotomy by percutaneous approach to the trigeminal ganglion, with severe intraoperative bleeding. Cavernous syndrome developed few hours later. Magnetic resonance imaging and digital subtraction angiography confirmed an indirect carotid cavernous sinus fistula, which was treated by one session of endovascular procedure using coils, achieving total occlusion of the fistula and total recovery of the symptoms. CONCLUSIONS: Embolization with coils is a minimally invasive, safe, and effective procedure for the treatment of carotid cavernous fistulas, including those related to iatrogenic causes.